Community stigma, victimization, and coping strategies among gay, bisexual, and other cis-gender men who have sex with men in slum communities in Ghana. BSGH-003 - Osman Wumpini Shamrock; Gamji Rabiu Abu-Ba'are; Edem Yaw Zigah; Henry Delali Dakpui; Gideon Adjaka; Natalie M. LeBlanc; Amina P. Alio; LaRon Nelson (BMC, 2024)
Abstract Background Gay, bisexual, and cis-gender men who have sex with men (GBMSM) face severe consequences, especially within stigmatized environments. However, very little is known about the experiences of GBMSM living in slums in SSA and Ghana. This study investigates the experiences of stigma, victimization, and coping strategies and proposes some interventional approaches for combating stigma facing GBMSM in slum communities. Methods We engaged GBMSM living in slums in two major Ghanaian cities. We used a time-location sampling and collected data through in-depth individual interviews. Two major themes emerged from the study: (1) insecurities and criminalization of GBMSM activity, and (2) GBMSM coping strategies. Results Findings show GBMSM experienced negative attitudes from the community due to their sexual behavior/orientation. GBMSM also developed coping strategies to avert negative experiences, such as hiding their identities/behavior, avoiding gender non-conforming men, and having relationships with persons outside their communities. Conclusion We propose interventions such as HIV Education, Empathy, Empowerment, Acceptance, and Commitment Therapy as possible measures to improve the experiences of GBMSM living in Ghanaian slum communities.